EARLY CHILHOOD EDUCATION REVIEWED FROM SOCIAL AND ECONOMIC COMMUNITY PERSPECTIVES - Futum Hubaib (Institut Pendidikan Tapanuli Selatan, 2020)
The background to the research starts from looking at gaps in social status in the community, the authors pay attention to, and claim that, children whose socioeconomic status is weak, almost do not enter kindergarten / early childhood education as appropriate. The purpose of this study is to look for the causes and reasons of their parents, whether due to their weak social or economic status. The method used by the authors in this study is a qualitative descriptive case study model, because the authors consider this method appropriate in approaching participants. During this study the authors examined 8 participants (parents of children), the time taken during the study was around 12 weeks. The results obtained after the completion of the study were, the authors found 5 analyzes of the main indicators including: social status, economic status, lack of information, no interest in children's schooling, and, do not know the benefits.